Entrepreneurial Human Capital and Persistence Underperforming Firms - Stephen Pembi; Ibrahim M Babbuli; Helen A Andow; Abduallsalam Jibril (International Journal of Entrepreneurship and Sustainability Studies, 2023)
Inadequate provision of human capital components mismatches between an employee’s capabilities and the job required to be perform. Also, inadequate communication or feedback between the employees and the management remains the major challenges to organizations regardless of their nature and sizes. These challenges could lead to persistence underperformance of organization if the fail to take into cognizance. Therefore, adequate provisions of human capital components are the fundamental solutions to the problems of firms’ underperformance. This study examines human capitals and their influence on firm performance; and to build a conceptual model that explains the relationship between human capital and firm performance. The study employed the used of qualitative method of research which is based on secondary sources of data. The results of the study signify that human capital variables (training, skills developments, knowledge management, motivation, work experience and quality of education) lead to human capital effectiveness and have significant effect on firm performance. Based on the findings it was recommended that firms should therefore, come up with effective motivational such as training opportunities, skill development, recognition, and pay benefits plans in providing various human capital components as not only does its direct organizations to achieve greater performance but also it ensures them to remain competitive for their long-term survival.